Employ lean leadership behaviors to enhance investment in human capital - Hussein, Hussein Waleed; Tanai Al-Zubaydi, Ghani Dahham (Journal of Economics and Administrative Sciences, 2021)
This research aims to determine the importance of the role that agile leadership plays in supporting programs and areas of investment in human capital, as it is the most important type of capital that the organization possesses and achieves returns that are many times the cost it bears, due to its rare and valuable characteristics. Through six behaviours: (humility behaviour, calm behaviour, wisdom behaviour, patience behaviour, objectivity behaviour, trust behaviour). As for investment in human capital, it was measured through its four elements (skills, knowledge, capabilities, experiences). Despite this, the researched organizations suffer from a decrease in awareness of the importance of this type of investment and the role of agile leadership in promoting it, and here the research problem arises, which the two researchers tried to address within the framework of the research objectives. The research has been applied in a number of Iraqi private colleges recognized by the Ministry of Higher Education and Scientific Research, and one of the most important justifications for this research is that the variables that it tries to study represent the contemporary foundations in managing and directing organizations so that they can control their internal resources and adapt to the external environment, and then Rationalize the investment decisions you make. The descriptive and analytical approach was adopted in the formulation and application of the research paragraphs, and the questionnaire was adopted as the main tool for data collection, which was prepared based on a number of ready-made criteria and indicators after adapting them to suit the Iraqi environment. And which were distributed to a sample of (227) members of the councils of private colleges that have been selected as the field of application, which are (24) colleges, and the Ready Program (SPSS) has been approved in the data processing. Among the most prominent conclusions he reached was that agile leadership exerts a moral influence in supporting investment programs with human capital. As for the originality/value of the research, it is represented in linking two variables (agile leadership, investment in human capital) in single research to provide its modest contribution to bridging the shortfall in the Iraqi library by providing a new source that combines these variables